Xiaomi Company / Muhammad Ikmal Ihsan - Ihsan, Muhammad Ikmal (2022)
This assignment is to identify the problem of the product which company that will be chosen in group of 5 students. For my group, we will be choosing Xiaomi Company as our representative company. Xiaomi has a lot of products, there is only one product to be chosen so I will be picking Xiaomi Mi Tv 3s 65 as product to be analysed. In this research, I have done the SWOT analysis in order to identify the strength, weakness, opportunities and threats of the Xiaomi Mi Tv 3s 65. In order to solve the problem Xiaomi Mi Tv 3s 65, I came up with an idea in order to solve this problem in this research.